Novel bent-core metallomesogens - Ames, Kelly (2005)
Novel polycatenar bent-core Schiff-base metallomesogens from derivatives of 1,1 O-phenanthroline ([MCb(LPhen-n)]), 2,2-bipyridine ([MCb(L Bipy-n)]) and 5,5'-dimethyldipyrromethane ((tc)_[M(LDipy-n)] and ex-[M(L Dipy-n)]) have been investigated in this body of work. The mesomorphic properties of these first- and second-row transition metal complexes have been studied. Further to the examination of the compounds in the liquid crystalline state, single crystal X-ray studies of short chain analogues were performed to determine the coordination geometry and the degree of selfassembly of the molecules in the solid state. Chapter 1 introduces the field of liquid crystals and metallomesogens, with a focus on thermotropic liquid crystals and their nomenclature, physical properties and applications. The historical background of the field is briefly explored and previous research on bent-core metallomesogens from the Schroder group in Nottingham has been reviewed. The characterisation of liquid crystalline mesophases, namely by polarised optical microscopy, differential scanning calorimetry and X-ray diffraction, are described. Further discussion is dedicated to the X-ray diffraction patterns generated by columnar mesophases. The chapter finishes with a description of the aims of the project. Chapter 2 commences with an introduction to liquid crystals derived from 1,1 O-phenanthroline. Following this is a description of the synthesis and characterisation of mesomorphic metal-free ligands, LPhen-n (n = 10, 12, 14, 16), four novel series of metallomesogens and two non-mesomorphic series of complexes derived from 1,10-phenanthroline, [MCb(LPhen-n)] (M = Mn2+, Fe2~, C02+, Ni2+, Cu2+. Zn2+~ LPhen = 2.9-bis-[3' A ',5' -tri(alkoxy)phenyliminon1ethyl]- 1,1 O-phenanthroline: n = 8, 10, 12, 14, 16). Structural determination by single crystal X-ray diffraction of the analogous methoxy complexes [MCb(LPhen-l)] (M = Mn2+, C02+, Ni2+, Zn2+), and the complex without any lateral aliphatic groups [CuCb(LPhen-O)], revealed the metal (II) complexes to have either distorted trigonal bipyramidal, square pyramidal or octahedral coordination geometry. The mesomorphic behaviour of the complexes [MCb(LPhen-n)] (M = Mn2+, C02+, Ni2+, Zn2+; n = 8, 10, 12, 14, 16) and the metal-free ligands LPhen-n (n = 10, 12, 14, 16) is columnar (with the exception of the non-mesomorphic [CoCb(LPhen-8)]), and the 2D symmetries of these mesophases vary between hexagonal, rectangular and oblique. Chapter 3 is introduced with a discussion of liquid crystalline compounds derived from 2,2' -bipyridine. Subsequently, the synthesis and characterisation of four new series of metallomesogens and two nonmesomorphic compounds derived from 2,2' -bipyridine, [MCb(L Bipy-n)] (M = Mn2+, Fe2+, C02+ Cu2+ and n = 16; M = Ni2+, Zn2+ and n = 10, 12, 14, 16; L Bipy = 6,6' -bis-[3' ,4',5' -tri(alkoxy)phenyliminomethyl]-2,2' -bipyridine) are detailed. Single crystal X-ray diffractometry revealed the coordination geometry• of [MnCb(LBipy-l)], [CoCb(LBipY-l)] and [NiCb(LBipy-l)] to be octahedral, whereas [ZnCb(LBipY-l)] is distorted trigonal bipyramidal. The complexes [MCb(L Bipy-n)] (M = Mn2+, C02+ and n = 16; M = Ni2+, Zn2+ and n = 10, 12, 14, 16) exhibit mesomorphic character and again generate columnar mesophases. Finally, Chapter 4 begins with a discussion on pyrrole-derived liquid crystals. Consequently, the synthesis and characterisation of hexacatenar d compoun s [M(LDipH/)] \: (M -- 2H ,Zn 2+, Pd2+.' n = 10 ,_l', 1'1"t o 16', x. = 1, ,-), tetracatenar compounds tc_[M(LDip~-16)1\ (M = 2H, Zn2+, Pd2T ; x = 1, 2) and extended dicatenar compounds ex_[M(LDipy-n)]x (M = 2H, Zn2+, Pd2+; x = 1. 2) are described. Characterisation by X-ray diffraction of single crystals of [Zn(LDipy-l)h, ex-[Zn(LDipy-l)h show they exhibit a distorted tetrahedral geometry, forming double stranded helical structures, while ex-[Pd(L Dipyl)] has a distorted square planar geometry. The metal-free ligands H2LDip~-1/ (n = 10, 12, 14, 16) and complexes [Zn(LDipy-16)h and [Pd(LDipy-n)] (n = 12, 14, 16) all exhibit narrow mesomorphic temperature ranges and unidentified mesophases. The tetracatenar compound tc_[Zn(LDipy-16)h generates a columnar hexagonal mesophase and the complex tc_[Pd(LDipy-16)] generates an unidentified liquid crystalline phase, whereas the metal-free ligand tc-H2L Dipy-16 has no mesomorphic character. Finally, two of the extended dicatenar compounds ex-H 2L DipY-16 and ex-[Zn(L Dipy-16)h are non-mesomorphic, while ex-[Pd(L Dipy-16)] was found to have a smectic A phase.